Effects of vagotomy and pharmacological blocking on heart rate of the toad Rhinella arenarum (Anura: Bufonidae) during forced submersion - Cervino, Claudio (2017)
Toads of Rhinella (=Bufo) arenarum were subjected to a condition of forced submersion duringa 40-minute period, to deepen the understanding of the mechanisms involved in the control ofboth submersion and emersion. Animals previously submitted to a first control measurementseries, were then injected with atropine or propranolol, or were vagotomized. In animals eitherinjected with atropine or vagotomized, a higher heart rate (HR) than in the control group wasobserved, before, during and after the forced submersion. These animals were able to decreaseHR, although in a lesser extent than controls, suggesting that other mechanisms in addition tovagal activity are also producing and maintaining bradycardia during the submersion period.In those animals injected with propranolol (a β-adrenergic blocker), a HR lower than that ofcontrols were observed only at the beginning of the submersion and during the emersion phase.The low HR caused by propranolol during emersion with buccal pumping shows the importanceof the sympathetic system in increasing HR during emersion.